2019
DOI: 10.35119/myjo.v1i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-DRB1*04 and Malay patients with Vogt-Koyanagi-Harada syndrome in Malaysia: A case-control study

Abstract: Introduction: Vogt-Koyanagi-Harada (VKH) is an autoimmune disorder affecting melanocyte-containing tissues. Major histocompatibility complex, class II, DR beta1 (HLA-DRB1)*04 and its suballele HLA-DRB1*0405 were found to be associated with VKH in many studies.Purpose: To determine the association of HLA-DRB1*04 and its suballele HLADRB1*0405 with VKH patients of Malay descent.Materials and methods: A case control study was conducted among VKH patients of Malay ethnicity attending Ophthalmology Clinic, Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Vogt-Koyanagi-Harada disease is an important cause of panuveitis, affecting, more frequently, pigmented skin individuals such as Amerindian, Hispanic [12,13], and Asian patients, including those from Japan [6], Singapore [10], and Malaysia [8]. K. Diallo et al, who conducted a multicentric study in France, found that North African was the primarily represented ethnicity 58%, followed by Southeast Asian 49%, Caucasian 20%, and Hispanic 2% [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vogt-Koyanagi-Harada disease is an important cause of panuveitis, affecting, more frequently, pigmented skin individuals such as Amerindian, Hispanic [12,13], and Asian patients, including those from Japan [6], Singapore [10], and Malaysia [8]. K. Diallo et al, who conducted a multicentric study in France, found that North African was the primarily represented ethnicity 58%, followed by Southeast Asian 49%, Caucasian 20%, and Hispanic 2% [13].…”
Section: Discussionmentioning
confidence: 99%
“…This disease has a strong genetic association with HLA-DRB1*0405 [5][6][7]. Eye involvement is usually bilateral [8,9] rather than unilateral.…”
Section: Introductionmentioning
confidence: 99%